(3GdchGcH hPhGJ GdPhGFH hJCKjQGJgGs ((3MGLi (B)(3Ydi GdQGRi (B) s)
(3ChdgG (B:s
(3ai Gdbhd Ydi GdchGcH hPhGJ GdPhGFH hJCKjQGJgG bGd HWdjehS GdMcje ai GdTeS hGdfjGRc hPhGJ GdPhGFH ef KhGfi GdfLhe hdjSJ efgG s
(3BNQgG (B:s
(3hbGd EPG cGf YWGQO ai GdJMhjd ai GdMed QGLY hefUQa hEPG cGf GdbeQ ai GdMhJ eJUdkG HGdeTJQi Ydi WGYI GdQYjI ddedc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdSGOSs
(3HChd GdeLehYg Jedc SfI (B1249s
(3HgG fXGe GdJYbjHIs
(3cJHJ gPg GdfSNI fbdkG Yf fSNI LeYgG EHQGgje GdMGSH GdeGdci GdefUhQi GdfGUQi HeOjfI GdbGgQI SfI (B759(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdadcs